Evaluation of Customer Satisfaction at Nina Pharmacy Padangsidimpuan City - vera, yulia; Insan, Hafni nur; Hasibuan, Elmi Sariani; Rangkuti, Juni Andriani (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2024)
A pharmacy is a pharmaceutical service facility where pharmaceutical practice is carried out by pharmacists, while pharmaceutical service is a direct and responsible service to patients related to pharmaceutical preparations. Providing pharmaceutical services is not just about providing medicines, but also ensuring that patients receive safe, effective and affordable treatment. The level of patient satisfaction is the patient's or service user's response to each health service provided. The aim of this research is to determine the level of patient satisfaction with pharmaceutical services at the Nina pharmacy in Padangsidmpuan City in 2024. This type of research is descriptive research using a research instrument in the form of a questionnaire whose validation and reliability have first been tested using 5 dimensions of satisfaction, namely responsiveness. ), reliability, assurance, empathy and direct evidence. The results of research at the Nina pharmacy in Padangsidimpuan City showed that the results were responsiveness (45.27%), reliability (44.44%), assurance (38.33%), empathy (44.44%), tangible (61.05%) . It can be concluded from the results of this research that Nina's health center received the satisfaction category.